Effect of Planting Media Composition and Dose of NPK Fertilizer on Growth and Yield of Shallots (Allium ascalonicum L.) - Eka Suzanna; Sunarti Sunarti; Pelya Nopriliyanti (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the effect of the composition of the planting media and the dose of NPK fertilizer on the growth and yield of shallots. This study was conducted in Rawa Makmur village of Bengkulu from December 2021 to March 2022. The design used was a completely randomized design (CRD) with 2 (two) treatments and three replications. The first treatment was the composition of the planting media, which consists of three levels, topsoil + manure (1:2), topsoil + rice husk (1:2) and topsoil + manure + rice husk (1:1:1). The second treatment was the dose of NPK fertilizer, which consists of three levels, 200 kg/ha, 250 kg/ha and 300 kg/ha. The results of the analysis of variance were continued with the Duncan's Multiple Range Test (DMRT) test with a test level of 5%. The results showed that the composition of the planting media had a very significant effect on the growth and yield of shallots except for variable the number of leaves 2 wap and the number of tillers per polybag. The best planting media composition treatment for the growth and yield of shallots was topsoil soil + manure (1:2). The treatment dose of NPK fertilizer significantly affected the number of leaves 6 wap. The best dose of NPK fertilizer for the growth of shallots was a dose of 300 kg/ha, with the highest number of leaves at 6 wap. The interaction of the treatment composition of the planting media and the dose of NPK fertilizer had no significant effect on the growth and yield of shallots.